Cardiac Cavity Tracking: CACCT: An Automated Tool of Detecting Complicated Cardiac Malformations in Mouse Models (Adv. Sci. 8/2020). Issue 8 (22nd April 2020) - Chu, Qing; Jiang, Haobin; Zhang, Libo; Zhu, Dekun; Yin, Qianqian; Zhang, Hao; Zhou, Bin; Zhou, Wenzhang; Yue, Zhang; Lian, Hong; Liu, Lihui; Nie, Yu; et al.
Abstract : In article number 1903592, Yu Nie, Shengshou Hu, and co‐workers establish an automated tool based on micro‐computed tomography (CT) images known as CACCT to identify complicated cardiac malformations in mice. With CACCT, researchers, even those without expert training or diagnostic experience of congenital heart diseases, can identify murine complicated cardiac malformations effectively, including transposition of the great arteries, double‐outlet right ventricle and atypical ventricular septal defect, whose accuracy is equivalent to senior fetal cardiologists.